Case of phenotype of optic nerve atrophy due to mutation in С19orf12 gene (neurodegeneration with the brain iron accumulation (nbia)) - M.E. Ivanova; V.V. Kadyshev; D.S. Atarshchikov; I.V. Zolnikova; N.P. Akchurina; N.K. Serova; F.A. Konovalov; E.R. Lozier; E.A. Pomerantseva; N.V. Vetrova; D. Barh; L.M. Balashova; et al. (РМЖ "Клиническая офтальмология")
M.E. Ivanova1, V.V. Kadyshev2, D.S. Atarshchikov3, I.V. Zolnikova4, N.P. Akchurina4, N.K. Serova5, F.A. Konovalov6, E.R. Lozier6, E.A. Pomerantseva7, N.V. Vetrova7, D. Barh8, L.M. Balashova9, J.M. Salmasi10 1 LLC “Oftalmic”, Moscow, Russian Federation 2 Research Centre for Medical Genetics, Moscow, Russian Federation 3 Central Clinical Hospital under Presidential Affairs, Moscow, Russian Federation 4 Moscow Helmholtz Research Institute of Eye Diseases, Moscow, Russian Federation 5 N.N. Burdenko National Medical Research Center of Neurosurgery, Moscow, Russian Federation 6 Independent Clinical Bioinformatics Laboratory, Moscow, Russian Federation 7 Center for Genetics and Reproductive Medicine “Genetiko”, Moscow, Russian Federation 8 Institute of Integrative Omics and Applied Biotechnology (IIOAB), Bangalore, India 9 Non-profit partnership International Scientific and Practical Center for the Proliferation of Tissues of Russia, Moscow, Russian Federation 10Pirogov Russian National Research Medical University, Moscow, Russian Federation The article describes the clinical case of optic atrophy due to a homozygous mutation in exon 3 of the C19orf12 gene (chr19: 30193863AACAGCCCCCCG> A, rs515726204), the frequency of which in the ExAC control sample is 0.0074. With this mutation, a frameshift occurs at 69-th position (p.Gly69fs, NM_001031726.3), which usually leads to neurodegeneration with the brain iron accumulation (NBIA), type 4 (OMIM: 614298). In described clinical case the main complaint of patient was visual impairment, with magnetic resonance imaging patient revealed only the expansion of the sellar fossa. The vision of 7-year-old boy decreased significantly for 2 years without any apparent reasons, spectacle correction did not give an improvement in vision to 100%. During the examination partial atrophy of the optic nerves was revealed, consultations were conducted with a neurologist, neurophthalmologist. Hyperreflexia, gait changes, and a slight delay in speech development were also revealed. No other clinical neurological symptoms were observed. The article describes a detailed ophthalmic clinical picture, discusses diagnostic and therapeutic tactics. Keywords: optic nerve atrophy, neurodegeneration with the brain iron accumulation, NBIA, mutation, gene, C19orf12. For citation: Ivanova M.E., Kadyshev V.V., Atarshchikov D.S. et al. Case of phenotype of optic nerve atrophy due to mutation in С19orf12 gene (neurodegeneration with the brain iron accumulation (nbia)). Russian Journal of Clinical Ophthalmology. 2020;20(1):–36. DOI: 10.32364/2311-7729-2020-20-1-33-36.